Human Cell Analyzer Automated Microscopic Inspection Using Image Processing and Machine Learning Techniques - Razali, Sheriza Mohd; Islam, Mohammad Sayful; Pria, Firuz Fatema (International Journal of Social Sciences: Current and Future Research Trends, 2025)
Restricted Access.